(untitled) (Scientific journal of the Fergana State University, 2024)
The growing population of the world has to fulfil its food needs day by day. One of the high quality foodstuffs that enrich the population with protein is fish products.In order to develop this area, extensive reforms are being carried out in our Republic. It follows that the study of species composition, bioecology of fish helminths, which seriously harm the increase of fish catch, is of great importance. It has become necessary to study helminths of fish in the Fergana Valley. In the course of research work the damaging properties of fish Cestoda, nematoda, trematoda, acanthocephalus were studied.